Does Innovative Behavior Condition The Impact Of Structural Empowerment On Entrepreneurial Success? - Sugiyanto, Eviatiwi Kusumaningtyas; Widjajanti, Kesi; Wijayanti, Ratna (Universitas Prasetiya Mulya, 2023)
This study aims to close the gap of previous research related to the impact of structural empowerment on business success. Apart from the research gap, this research departs from the phenomenon of the large entrepreneurial potential of women in Indonesia which can be supported by empowerment programs. To close the research gap, innovative behavior is used as a mediating variable between the influence of structural empowerment and business success. Data was collected via Google form on 96 women entrepreneurs. The sample is determined through purposive sampling. The analysis tool used is SEM with the Wrap PLS 8.0 program. The research results show that both structural empowerment and innovative behavior influence business success, and innovative behavior has succeeded as a mediating variable in this research.